DIGITAL MARKETING SEBAGAI STRATEGI PEMASARAN DI ERA SOCIETY 5.0: SEBUAH LITERATURE REVIEW - Rudy Haryanto; Arief Setiawan; R. Nurhayati; I Gede Agus Mertayasa; Aat Ruchiat Nugraha (ITB AAS Indonesia Surakarta, 2024)
Rapid technological developments have changed business paradigms and interactions with consumers, encouraging the emergence of the concept of Society 5.0. This era emphasizes technological integration and collaboration between humans and machines. In the era of Society 5.0, digital marketing is the key to success for companies in achieving business goals. This article discusses basic digital marketing concepts, key marketing strategies, successful implementation, challenges, and solutions in running digital promotions. Through qualitative literature study methods, this article analyzes various sources to understand these concepts. The results show that identifying the target audience, creating relevant content, using digital channels, and digital analytics are the keys to success in digital marketing. In the Society 5.0 era, companies need to adopt a business strategy that includes advanced technology, a focus on user experience, collaboration, sustainability, and transformation to a platform-based business model. Nevertheless, companies are faced with challenges such as technological complexity, fierce competition, data security, changing trends, and limited resources. To overcome these challenges, companies need to have a deep understanding of trends and technology, creativity in strategy development, commitment to data security, and flexibility in adapting. In this way, companies can run digital marketing promotions more effectively and achieve marketing goals in today's digital era.